Partisipasi masyarakat dalam manajemen bencana di Kota Surakarta - Joko Pramono; Joko Suranto (Universitas Merdeka Malang, 2021)
This study explores community participation in disaster management in Surakarta. The method used in this research is descriptive qualitative with interactive data analysis. The research data is in the form of primary and secondary data which were extracted through interviews, observation and documentation. The research flow includes literacy studies, field studies, problem identification and problem formulation, data collection, data processing, data analysis, reports and publications. The results showed that community participation in disaster management was evident at the disaster management stage. Communities together carry out rescue, evacuation and provision of emergency posts or evacuation. The community also works together in providing all the needs of the affected residents. Participation is not optimal in the pre-disaster and post-disaster stages. This is due to the lack of public awareness, the absence of firm sanctions and the absence of a forum for the community to work together with the government to plan and evaluate disaster activitie